Determinants of Carbon Emissions in 10 ASEAN Countries - Ermatry try Hariani; Retno Febriyastuti Widyawati; Andi Lopa Ginting (Economics Development Analysis Journal, 2022)
Rapid economic development in ASEAN countries from many aspects of the global economy and energy outlook. Increased consumption of fossil fuels leads to an increase in CO2 emissions (ACE, 2021). The problem of increasing CO2 caused by economic development in ASEAN needs to be studied more deeply what variables will in the economic development affect the increase in CO2 emissions. The purpose of this study is to test and obtain empirical evidence on determinants of carbon emissions in 10 ASEAN Countries (Brunei Darussalam, Indonesia, Cambodia, Lao PDR, Myanmar, Malaysia, Philippines, Singapore, Thailand, Vietnam) during 2010-2018. Some of the factors that were taken in this study, there are Gross Domestic Product (GDP), total population (PDDK), and industrial growth (MANF). This study uses panel data (time series and cross section). In using the method of regression of panel data is performed uji chow and uji hausman, and elected, namely the fixed effect model. Results of the study proved that all independent variables (GDP, total population, industrial growth) have a significant effect on carbon emissions. The conclusion is that by looking at all the independent variables in this study that affect the increase in CO2 emissions, it must be considered in the future how to control these variables in order to reduce CO2 emissions. The findings of this study are that the variables of GDP, total population and industrial growth cause an increase in CO2 emissions, this is in accordance with the theory.